Теоретичні засади управління грошовими активами підприємства - Височіна, Л. В. (НТУ "ХПІ", 2014)
Розглянуто особливості та механізм здійснення управління грошовими активами й платоспроможністю підприємства, виявлено основні його напрями, принципи та функції; а також розглянуто механізм визначення оптимального розміру залишку грошових активів підприємства. Запропоновано теоретичні положення щодо оптимізації системи управління грошовими потоками як одного з елементів в оцінці фінансового стану підприємства.

The article presents system for management of an enterprise’s cash flows which include the aims, the tasks, functions, methods and instruments. It is established, that one of the basic methods of improvement of cash flows management is optimization of their volume, allowing to raise efficiency of operating activity and to free cash means for realization of capital investments in enterprise development. Features and mechanism of realization of management of money assets and solvency of enterprise are considered, his basic directions, principles and functions, are educed; and also the mechanism of determination of optimal size of balance of money assets of enterprise is considered.
Theoretical principles of management of money assets of enterprise
Keywords: платоспроможність; цінні папери; оптимальний розмір; форми господарювання; money assets; solvency; securities; optimal size; management